Nasty beauty - Mohtarrudin, Norhafizah; Kassim, Fauziah; Ahmad Sharifuddin, Fatimah (Universiti Putra Malaysia Press, 2016)
A brain tumour is formed from an abnormal growth of cells in the brain that multiplies in an uncontrollable way. It can either be cancerous (malignant) or non-cancerous (benign). Though non-cancerous, the tumour could be fatal if it is located at the vital region of the brain. Brain tumours affect people of any age including children even though they tend to be more common in older adults.